OP0065 Nurse-led vaccination program dramatically improves pneumococcal vaccination coverage among patients with chronic inflammatory rheumatic diseases: a prospective pilot study. (15th June 2017) - Goulenok, T; Serre, J; Francois, C; Haegen, M-C Van der; Alexandra, J-F; Papo, T; Sacre, K
Abstract : Background: Patients with chronic inflammatory rheumatic diseases (IRD) receiving immunosuppressive therapy are at high risk for invasive pneumococcal disease. Despite national recommendations regarding pneumococcal vaccination, vaccination rate remains low in this population. Objectives: We aimed to determine whether a nurse-led vaccination program improve pneumococcal vaccination coverage among patients with chronic IRD. Methods: From April to August 2015, all consecutive adult patients with a chronic IRD admitted in our day hospital unit (Department of Internal Medicine, Bichat Hospital, Paris, France) were screened. Eligibility for pneumococcal vaccination was assessed according to French national recommendations. Patients were identified as candidate for pneumococcal vaccination, informed on the benefice and risk of vaccination and vaccinated by nurses. Pre-intervention (i.e. percentage of patients candidate for vaccination vaccinated before the intervention program) and post-intervention (i.e. percentage of patients candidate for vaccination vaccinated after the intervention program) pneumococcal vaccination rate were compared using Chi2 test. Results: 126 consecutive patients (43 [24–89] years, 61.9% females) with a chronic IRD were admitted in our day hospital unit during a 4 months period. Among them, 76 (60.3%) patients were candidate for pneumococcal vaccination because receiving prednisone, immunosuppressive drugs and/or biotherapy. The pre-intervention pneumococcal vaccination rate was 17.1 (13/76) %. Among patients candidate for pneumococcal infection but not vaccinated (n=63), 56 (88.9%) were accurately identified by nurses. Ten patients refused to be vaccinated and 46 eventually received pneumococcal vaccination. The post-intervention pneumococcal vaccination was 77.6 (59/76) % (p<0.001 as compared to the pre-intervention rate). Conclusions: Nurse-led vaccination program dramatically improves pneumococcal vaccination coverage among patients with chronic IRD. Disclosure of Interest: None declared